SOYBEAN RESISTANCE TO DROUGHT AND OTHER STRESS FACTORS - Soatova Shoxsanam Lolaboy qizi; Akram Jovlievich Ibragimov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The growth and development of soybean and the quality and composition of the crop are highly influenced by external environmental factors. Each influencing factor differs from one another according to its characteristics. It should be said that the soybean plant does not choose a place according to its biological characteristics. It also grows in saline, cultivated fields with elevated groundwater levels. It is also very convenient to care for it in a mixed way.